The Effect of E-Learning-Based Training and Organizational Culture on Employee Performance with Motivation as an Intervening Variable at PT. CBA Chemical Industry, Serang Regency - Alex Alex; Fathurrahman Fathurrahman; Murtianingsih Murtianingsih (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The rapid advancement of technology has driven the manufacturing industry, including the agrochemical sector, to optimize employee performance through digital training and the reinforcement of organizational culture. PT. CBA Chemical Industry has implemented e-learning-based training and developed internal corporate values; however, the performance of production operators has yet to show consistent improvement. This indicates a potential issue in the effectiveness of the training and cultural strategies implemented. This study aims to examine the influence of e-learning-based training and organizational culture on employee performance, with work motivation as a mediating variable. A quantitative approach was employed, using survey methods with questionnaires distributed to 81 production operators. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings reveal that e-learning-based training does not have a significant direct effect on performance or work motivation, while organizational culture significantly influences both. Work motivation also has a significant direct effect on performance but does not mediate the relationship between training or culture and performance. These results indicate that direct influences are more dominant than indirect effects through motivation. The study draws on motivational theories from Maslow, Herzberg, McClelland, and McGregor, which explain that training and organizational values can shape employee behavior, although their effectiveness is largely determined by how individuals perceive organizational stimuli.